2006
DOI: 10.1111/j.1750-3841.2006.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Potato Color and Texture Development during Baking, Frying, and Microwaving with the Addition of Liquid Smoke

Abstract: The rate of color and texture development in par‐fried French fries coated with liquid smoke and thermally processed was determined. Liquid smoke containing 8% to 11% carbonyls was diluted to 30% and applied to 1 side of French fries at 0%, 1%, 3%, or 5% by weight. The fries were immersion fried at 190.6 °C for 4 min, microwaved (900 watts) for 4 min, or baked at 190.6 °C for 20 min. Color and texture measurements were recorded at intervals during processing. Liquid smoke increased the rate of browning in Fren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…However, increasing the concentration of the liquid smoke from 1 to 5% did not affect the reaction rate because carbonyls were no longer the limiting reactant. Similar results have also been found with liquid smoke applied to French fried potatoes (Yost et al. 2006).…”
Section: Resultssupporting
confidence: 86%
“…However, increasing the concentration of the liquid smoke from 1 to 5% did not affect the reaction rate because carbonyls were no longer the limiting reactant. Similar results have also been found with liquid smoke applied to French fried potatoes (Yost et al. 2006).…”
Section: Resultssupporting
confidence: 86%
“…For both responses, good fit of data was obtained at all evaluated temperatures, with RMS values between 4.4% and 12.5% and 2.6% and 7.4%, for color change and polar compound generation, respectively. The specific rates of color change and polar compound generation presented similar magnitude (Table ) to those reported before by (Gupta and others ; Moyano and others ; Saguy and others ; Yost and others ), to describe the kinetics of nonenzymatic browning and lipid oxidation in fried potato, respectively.…”
Section: Resultssupporting
confidence: 75%
“…Adequacy of zero-order reaction kinetics for NEB was also reported in dehydrated carrots (Koca et al 2007) and pear puree (Ibarz et al 1999). However, Yost et al (2006) concluded pseudo zero-order reaction kinetics for the colour development of French fries coated with liquid smoke.…”
Section: Non-enzymatic Browningmentioning
confidence: 99%